Perancangan Aplikasi Waste Bank dengan Teknologi Blockchain - M. Fajar Wirayudha; Paniran Paniran (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
The growth of blockchain technology has created significant demand for Solidity developers, especially in the development of smart contracts. This research presents the latest data regarding the surge in job vacancies for Solidity Blockchain Developers in Indonesia, highlighting more than 5,000 vacancies in October 2022 according to Tech in Asia. Meanwhile, a report from the United Nations Environment Agency (UNEP) confirms the escalation of the global plastic waste and waste problem. With more than 380 million tons of plastic waste generated every year, and only a small portion being recycled, plastic waste poses a serious threat to marine and terrestrial ecosystems. In addition, the impact of climate change is increasing with methane produced from organic waste in conventional landfills.